Pengaruh Penambahan Serat Sabut Kelapa Pada Kuat Tekan dan Kuat Tarik Belah Beton Self Compacting Concrete - Sulwan Permana; Yusri Fisabili Shaffan (Institut Teknologi Garut, 2025)
Previous researchers have tried to find alternative concrete mixtures that are economical and environmentally friendly. One of the alternative additives developed is coconut fiber waste. The purpose of adding coconut fiber is to determine its effect on testing the compressive strength and split tensile strength of SCC (Self Compacting Concrete) concrete with a mixture percentage of 6%, 8%, and 10%. As for the addition of chemical substances, superplasticizer admixture aims to facilitate SCC concrete in achieving a qualified slump flow value. Research method. The research method applied is experimental compressive strength and split tensile strength of concrete with cylindrical shape with a mixture of added materials. The results of compressive strength testing obtained a normal concrete value of 16.30 MPa, then a mixture of 6% coconut fiber with a value of 17.26 MPa increased the normal concrete value by 5.88%, 8% coconut fiber with a value of 15 MPa decreased by 7.98%, and 10% coconut fiber with a value of 6.61 MPa decreased by 59.51%. For the tensile strength test results, obtained normal concrete worth 6.29 MPa then 6% coconut fiber mixture with a value of 7.10 MPa increased against the normal concrete value by 12.88%, 8% coconut fiber mixture concrete with a value of 6.60 MPa increased by 4.93%, and 10% coconut fiber mixture concrete with a value of 3.33 MPa decreased by 47.54%.